Antiviral antibody responses to systemic administration of an oncolytic RNA virus: the impact of standard concomitant anticancer chemotherapies. Issue 7 (22nd July 2021) - Roulstone, Victoria; Mansfield, David; Harris, Robert J; Twigger, Katie; White, Christine; de Bono, Johann; Spicer, James; Karagiannis, Sophia N; Vile, Richard; Pandha, Hardev; Melcher, Alan; Harrington, Kevin
Abstract : Background: Oncolytic reovirus therapy for cancer induces a typical antiviral response to this RNA virus, including neutralizing antibodies. Concomitant treatment with cytotoxic chemotherapies has been hypothesized to improve the therapeutic potential of the virus. Chemotherapy side effects can include immunosuppression, which may slow the rate of the antiviral antibody response, as well as potentially make the patient more vulnerable to viral infection. Method: Reovirus neutralizing antibody data were aggregated from separate phase I clinical trials of reovirus administered as a single agent or in combination with gemcitabine, docetaxel, carboplatin and paclitaxel doublet or cyclophosphamide. In addition, the kinetics of individual antibody isotypes were profiled in sera collected in these trials. Results: These data demonstrate preserved antiviral antibody responses, with only moderately reduced kinetics with some drugs, most notably gemcitabine. All patients ultimately produced an effective neutralizing antibody response. Conclusion: Patients' responses to infection by reovirus are largely unaffected by the concomitant drug treatments tested, providing confidence that RNA viral treatment or infection is compatible with standard of care treatments.